Modernisasi Melunturkan Kepercayaan Masyarakat Suku Jawa Yang Mengarah Pada Kehidupan Sekuler - Jahra Sinaga, Fadhillatu; Ade Chandra, Fadhlin (DAWUH : Islamic Communication Journal, 2021)
The rapid development of modernization towards the flow of technological advances makes the Javanese tribal society gradually eliminate mystical beliefs so that religious rituals are rarely carried out except for the royal family who still carry out these religious rituals. A life that puts the world first is secular. At first, many Javanese people believed in ancestral customs, although basically the Javanese people had religion, such as witchcraft, wangsit and other mystical things. Javanese society prioritizes harmony and respect as an effort to maintain the harmony of life "the principle of conflict prevention". The self-identity that is formed is expressed through thoughts and actions that are total, grounded and reasoned. However, in connection with the development of the times, the customs regarding these beliefs began to fade due to the development of the times and the world of education so that currently the number of public presentations who have a perception of the truth of these customs has been much reduced.